PERFORMANCE REVIEW OF GUJARAT STATE ROAD TRANSPORT CORPORATION - DR. SHILPA TRIVEDI (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
GSRTC serves the role of lifeline across the state of Gujarat. Over past 52 years of its existence, it has proved to be a dependable mode of transportation in every nook and corner of the state. It is providing services in most of the rural areas of the state. The environment has thrown up GSRTC to the challenges like productivity improvement, mark orientation and financial engineering. GSRTC has been trying hard to face the new challenges through vigorously pursuing a process of technical and managerial up gradation. But, financial viability has become a critical goal. Various controllable and uncontrollable factors affect the performance of the GSRTC. It is hypothesized that by controlling at least controllable factors GSRTC can improve its operational performance and thereby financial position. The main motto behind performance review of GSRTC is to contribute in improving performance of GSRTC and create value for all stakeholders, public, employees, vendors, state government and fund providers.